2021
DOI: 10.30684/etj.v39i3a.1777
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Components of Residential Solid Waste in Baqubah City and their Generation Rate

Abstract: Municipal solid waste is of variable, non-uniform inconsistent nature and the method by which the sample to acquire is decisive if the results are to be reliable. For data collection, an integrated methodological approach was introduced, including field investigation, questionnaire survey, and personal interviews, which were employed to estimate the rate of waste production and physical composition at the source of generation. Samples were collected from different socio-economic clusters (socio-income level). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…This study found the resistance of (glass/epoxy) samples was remain constant without any change after the immersion in the corrosive conditions.Composites reinforced by glass particles show an increase in some physical and mechanical properties when compared to elegant epoxy resin. The value of measured density for composite is obtained about 1.78 g/cm 3 . Modulus of elasticity and Vickers hardness value highest increased by (62%, 33%) respectively for composite at room temperature.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…This study found the resistance of (glass/epoxy) samples was remain constant without any change after the immersion in the corrosive conditions.Composites reinforced by glass particles show an increase in some physical and mechanical properties when compared to elegant epoxy resin. The value of measured density for composite is obtained about 1.78 g/cm 3 . Modulus of elasticity and Vickers hardness value highest increased by (62%, 33%) respectively for composite at room temperature.…”
Section: Discussionmentioning
confidence: 89%
“…After immersion density fluctuate in epoxy pure as well as after post cured at 50 ° C, one of the initial strategies for improving the dimensional stability of composites was to attribute it to heat or thermal treatment [16]. The value of measured density for composite is obtained about 1.78 g/cm 3 , and remains constant during the immersion period at room temperature and 50°C . Figure (5) shows that the composite density cured at room temperature and at 50° C, before and after the immersion remain constant without any change after immersion in five solutions .…”
Section: -3density Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been a number of studies published on the quantity, characteristics, thermal production, composting and recycling of solid waste in Erbil City [2,[4][5][6][7][8][9]. Also, several pieces of research on domestic solid waste generation, MSW properties and management have been published in other provinces in Iraq [10][11][12][13][14][15][16][17][18][19]. Monney et al [20] studied household solid waste characteristics in Wa, an urban community in Ghana.…”
Section: Introductionmentioning
confidence: 99%